The impact of culturally acquired behavioral norms on workplace communication. - Nussbaum, George F. (My University, 2004)
This study explored cultural diversity influences on the concepts of time and punctuality; allowable limits of expressiveness; kinesics and oculesic cues; request/response time; and ethnic and gender preferences for supervisors. The research was conducted using participant volunteer personnel in a large U.S. Army Medical.

Using the theoretical background of Blumer's Symbolic Interactionalism, thirty-two volunteer participants were individually interviewed in a qualitative, grounded theory research design study. The study population consisted of active duty military personnel with equal representation of males and females and officers and enlisted personnel from African-American and Euro-American heritage. Analysis of the data revealed a central theme of interpersonal relationship expectations. The responses provided in four vignettes exploring time, punctuality, expressiveness, kinesics and oculesic characteristics, request/response time, and preference choices for supervisors revealed that the African-American participants communicated workplace relationship efforts with an orientation toward an interpersonal approach (collectivistic). The participants from Euro-American heritages approached most workplace relationships from a "business only" perspective (individualistic). The findings suggest that relationship expectations have a cultural basis in some of the miscues in work environment communication. Further research among other population and ethnic groups to corroborate this theory.
Keywords: Intercultural communication United States.; Sociology, Industrial and Labor Relations.; Symbolic interactionism.; Whites United States Psychology.; Interpersonal relations United States.; African Americans Psychology.; Business Administration, Management.; Speech Communication.; Sociology, Ethnic and Racial Studies.; Communication in organizations.